A new effective metric for dynamical robustness of directed networks - Sun, Jiashuo; Xiang, Linying; Chen, Guanrong (Frontiers in Physics, 2023)
In this article, dynamical robustness of a directed complex network with additive noise is inverstigated. The failure of a node in the network is modeled by injecting noise into the node. Under the framework of mean-square stochastic stability, a new robustness metric is formulated to characterize the robustness of the network in terms of synchronization to the additive noise. It is found that the node dynamics plays a pivotal role in dynamical robustness of the directed network. Numerical simulations are shown for illustration and verification.